DaVinci Resolve: Software Features and Workflows. - Inhofer, Patrick (linkedin.com, 2021)
Ready to go beyond the basics of DaVinci Resolve? Tune into this course to learn workflows and techniques for getting the platform to work precisely how you want it to.